English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2 answers

hi

suppose

1)x = cos t + 4
2)y= sin (2t)

from 1)
cos(t) = x - 4
sin(t) = root( 1 - (x-4)^2)
sin(2t) = 2 sin(t) cos(t) = 2*(x-4)*root( 1 - (x-4)^2)

then
y =2*(x-4)*root( 1 - (x-4)^2)
y^2 =4*(x-4)^2*( 1 - (x-4)^2)

4*grade function

bye

2007-04-17 12:42:14 · answer #1 · answered by railrule 7 · 0 0

cos x= x-4 and y= 2sinx*(x-4)
so
cos x=x-4
sin x= y/2(x-4)
square both sides and sum
1=(x-4)^2+y^2/4(x-4)^2 so
4(x-4)^4-4(x-4)^2+y2=0

2007-04-17 19:50:04 · answer #2 · answered by santmann2002 7 · 0 0

fedest.com, questions and answers